2013
DOI: 10.1007/s00268-013-1942-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Early Surgical and Oncologic Outcomes after Total Gastrectomy with “Over‐D1” Lymphadenectomy for Gastric Cancer

Abstract: Obese patients with operable gastric cancer can be candidates for standard extensive surgical resection, provided that pre-existing co-morbidities and potential intraoperative and postoperative complications are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 59 publications
(85 reference statements)
3
23
2
Order By: Relevance
“…This is in accordance with our own data, although perioperative costs have not been specifically analyzed; however, our study showed a significantly longer length of hospital stay for obese patients, resulting from higher postoperative morbidity rates, and thus, we assume higher postoperative costs in the obese patient group. Our data is further supported by a study on the impact of obesity on surgical and oncologic outcomes by Pata et al [27] , who showed longer operative times and more medical and surgical complications in obese patients (BMI >25). However, their multivariate analysis on 161 patients undergoing total gastrectomy for cancer could not identify obesity as an independent risk factor for postoperative complications.…”
Section: Discussionsupporting
confidence: 75%
“…This is in accordance with our own data, although perioperative costs have not been specifically analyzed; however, our study showed a significantly longer length of hospital stay for obese patients, resulting from higher postoperative morbidity rates, and thus, we assume higher postoperative costs in the obese patient group. Our data is further supported by a study on the impact of obesity on surgical and oncologic outcomes by Pata et al [27] , who showed longer operative times and more medical and surgical complications in obese patients (BMI >25). However, their multivariate analysis on 161 patients undergoing total gastrectomy for cancer could not identify obesity as an independent risk factor for postoperative complications.…”
Section: Discussionsupporting
confidence: 75%
“…18 In contrast, studies in patients after TG showed that an increased BMI was associated with greater blood loss, longer operation times, and increased rate of postoperative morbidity. 19,20 Although all of these studies used BMI alone without measurement of VFA as a parameter for obesity, results in these studies support our findings above. We consider that visceral fat is likely to have crucial influence on operative procedures during TG rather than DG.…”
Section: Discussionsupporting
confidence: 84%
“…This effect could improve glucose control postoperatively, which has been demonstrated to reduce the risk of infectious complications. The higher rate of complications associated with obesity in surgery for gastric cancer is mainly attributed to an increase in the rate of surgical‐site infections . The significantly reduced HbA1c concentration in our study supports the concept that preoperative weight loss programs may reduce postoperative infectious complications.…”
Section: Discussionsupporting
confidence: 81%